1950
DOI: 10.1042/bj0470149
|View full text |Cite
|
Sign up to set email alerts
|

Studies on suramin. 8. The action of the drug on enzymes and some other proteins. General considerations

Abstract: GLUTAMATE AND POTASSIUM TRANSPORT 149 depleted of its normal potassium content, small increases occurred on incubation with the two substrates. 6. It is suggested that glucose (or lactate or pyruvate) is required as a source of energy; whilst L-glutamate serves another function in potassium transport. We wish to thank Dr W. Klyne for information on the flame photometer of Domingo & Klyne (1949) and for instruction in its use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

1951
1951
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(7 citation statements)
references
References 9 publications
0
6
1
Order By: Relevance
“…Previous extensive studies have shown that suramin (compound I) binds to plasma proteins and inhibits certain enzymes, probably by interaction of the sulphonic acid groups with the basic groups of the protein (Spinks, 1948;Wilson & Wormall, 1949;Town, Wills, Wilson & Wormall, 1950;. Such a mechanism may well explain the inhibition of a-toxin, especially by compounds of group 1, although the results of the present study suggest that the sulphonic acid groups alone do not govern the degree of inhibition.…”
Section: Resultscontrasting
confidence: 61%
“…Previous extensive studies have shown that suramin (compound I) binds to plasma proteins and inhibits certain enzymes, probably by interaction of the sulphonic acid groups with the basic groups of the protein (Spinks, 1948;Wilson & Wormall, 1949;Town, Wills, Wilson & Wormall, 1950;. Such a mechanism may well explain the inhibition of a-toxin, especially by compounds of group 1, although the results of the present study suggest that the sulphonic acid groups alone do not govern the degree of inhibition.…”
Section: Resultscontrasting
confidence: 61%
“…In the case of suramin, it was found that the drug binds with no domain-specific interactions and with no selectivity, and thus the protein-suramin interaction is non-specific [11]. It has been known for some time that suramin will bind with high affinity to serum albumin [12]. Preincubation of HIV-1 RT with template/primer, dNTP or a combination of the two will not protect the enzyme from inactivation by (-)epicatechin 3-gallate (results not shown), further suggesting that the interaction is non-specific.…”
Section: Discussionmentioning
confidence: 99%
“…Several suramin analogs have been developed subsequently with the aim of improving selectivity for P2X 1 receptors, because blockers of P2X 1 receptors on platelets hold promise as antithrombotic agents (15,16). One of these is 4,4Ј,4Љ,4ٞ-(carbonylbis(imino-5,1,3-benzenetriylbis(carbonylimino)))tetrakis-benzene-1,3-disulfonic acid (NF449), 2 which blocks P2X 1 receptors in low nanomolar concentrations and has good selectivity over P2X 3 receptors (17,18).…”
Section: Suramin (8-[(4-methyl-3-{[3-({[3-({2-methyl-5-[(468-trisulmentioning
confidence: 99%